Optimization and Performance Analysis of a Geothermal-Based Power Generation System Based on Flash-Binary and Dual-Pressure Evaporation Organic Rankine Cycles Using Zeotropic Mixtures - Mojtaba Nedaei; Abolfazl Keykhah; Borzo Kamary; Ehsanolah Assareh (Advances in Engineering and Intelligence Systems)
Population growth worldwide in recent decades has increased the demand for power. Geothermal energy provides a reliable and stable reservoir for power generation. This paper proposes an integration of single-flash geothermal with a dual-evaporation organic Rankine cycle (D-ORC) to generate power. The system’s performance is estimated via thermodynamic and thermoeconomic analyses. Five different zeotropic mixtures are considered the D-ORC working fluid, and their performance is compared at the optimum state. Perfluoropentane/butene presents the best performance indexes and is considered the D-ORC’s working fluid. Hence, the proposed system provides 7992.29 kW of net power with 62.42% exergetic efficiency. Also, the exergoeconomic performance indicates that the net present value and payback period are about 10.85 million dollars and 3.47 years, respectively. Also, the net present value of the proposed system is estimated for the four electricity sale and geofluid prices and reveals that the product sale costs influence the system’s economic performance more than the purchase cost. The exergy destruction distribution in the employed components is shown as the Grassmann diagram. The steam turbine has the highest exergy destruction of about 996 kW, and the first expansion valve with 714 kW of exergy destruction is the next one. Also, the condensers contain considerable exergy destruction, about 26.98% of total exergy destruction.